2014
DOI: 10.1039/c4cc01287a
|View full text |Cite|
|
Sign up to set email alerts
|

Self-decoration of Pt metal particles on TiO2 nanotubes used for highly efficient photocatalytic H2 production

Abstract: Pt decorated TiO 2 has, over the past decades, been a key material for photocatalytic hydrogen production. The present work shows that growing anodic self-organized TiO 2 nanotubes from Ti-Pt alloy with a low Pt content of 0.2 at% leads to oxide nanotube layers that are self-decorated with Pt nanoparticles of 4-5 nm in diameter. The average particle spacing is in the range of~50 nm and is partially adjustable by the anodization conditions. This intrinsic decoration of TiO 2 nanotubes with Pt leads to a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
(25 reference statements)
2
47
0
Order By: Relevance
“…Their work showed that both doped and metalized samples had similar photocatalytic activity [59]. Self decorated Pt (0.2 at%) metal deposits on the surface of TiO 2 prepared by anodization of Ti-Pt alloy for 2 h exhibited enhanced photocatalytic hydrogen evolution under both UV/visible light irradiation [61]. These Pt nanoparticle deposits were found to have a diameter of 4-5 nm with inter particle spacing of ∼50 nm and these dimensions were partially adjustable by changing anodization conditions.…”
Section: Photocatalytic Activity Of Platinum Deposited Titania (Pt/timentioning
confidence: 99%
See 1 more Smart Citation
“…Their work showed that both doped and metalized samples had similar photocatalytic activity [59]. Self decorated Pt (0.2 at%) metal deposits on the surface of TiO 2 prepared by anodization of Ti-Pt alloy for 2 h exhibited enhanced photocatalytic hydrogen evolution under both UV/visible light irradiation [61]. These Pt nanoparticle deposits were found to have a diameter of 4-5 nm with inter particle spacing of ∼50 nm and these dimensions were partially adjustable by changing anodization conditions.…”
Section: Photocatalytic Activity Of Platinum Deposited Titania (Pt/timentioning
confidence: 99%
“…These Pt nanoparticle deposits were found to have a diameter of 4-5 nm with inter particle spacing of ∼50 nm and these dimensions were partially adjustable by changing anodization conditions. Samples prepared at shorter (∼30 min) and longer (∼4 h) anodization time periods exhibited lower hydrogen production which indicates the need of optimum size with particle interspacing for effective photocatalytic performance [61]. (Table 2).…”
Section: Photocatalytic Activity Of Platinum Deposited Titania (Pt/timentioning
confidence: 99%
“…An elegant decoration approach for anodic nanotubes with noble metal particles is using low concentration Ti-X (X=Au,Pt) alloys 27,537 that can provide very uniform particle densities and defined particle diameters.…”
Section: Conversion Of Tubesmentioning
confidence: 99%
“…Currentd ata indicateaproductivity at best of approximately 0.2-0.5 g H 2 m À2 h À , [110,120] but the value is often much lower.A s an example reporting highly efficient photocatalytic H 2 production, the resultso fS chmuki et al [121] shouldb ec ited. For Ptdoped TiO 2 nanotubes under solar simulator illumination (100 mW cm À2 ), ap roductivity of approximately 0.01 g H 2 m À2 h À1 is reported, whichi ncreasest oa pproximately 0.06 g H 2 m À2 h À1 under UV light (laser,3 25 nm, 60 mW cm À2 )i llumination.…”
Section: Cost Effectiveness Of Peca Cellsmentioning
confidence: 97%